2018
DOI: 10.1016/j.ymthe.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Endothelial Progenitor Cells Improve the Outcome of a Murine Model of Sepsis

Abstract: Microvascular dysfunction leads to multi-organ failure and mortality in sepsis. Our previous studies demonstrated that administration of exogenous endothelial progenitor cells (EPCs) confers protection in sepsis as evidenced by reduced vascular leakage, improved organ function, and increased survival. We hypothesize that EPCs protect the microvasculature through the exosomes-mediated transfer of microRNAs (miRNAs). Mice were rendered septic by cecal ligation and puncture (CLP), and EPC exosomes were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(163 citation statements)
references
References 51 publications
4
152
0
Order By: Relevance
“…Furthermore, exosomes had been shown to carry different nucleic acids, including microRNAs (miRNAs), which are acquired by recipient cells to regulate their own fate [10,11]. Previous studies found that miRNAs in exosomes from endothelial progenitor cells improved outcomes of patients with cardiovascular disease [12] and lipopolysaccharide-induced acute lung injury [13] and also of a murine model of sepsis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exosomes had been shown to carry different nucleic acids, including microRNAs (miRNAs), which are acquired by recipient cells to regulate their own fate [10,11]. Previous studies found that miRNAs in exosomes from endothelial progenitor cells improved outcomes of patients with cardiovascular disease [12] and lipopolysaccharide-induced acute lung injury [13] and also of a murine model of sepsis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou found in the experiment that exosomes miR-126-5p and 3p can inhibit LPS-induced human microvascular endothelial cells (HMVECs) high mobility group protein b1 (HMGB1) and vascular cell adhesion molecule 1 (VCAM1) levels, It was confirmed that the use of EPR exosomes to deliver miR-126 can prevent microvascular dysfunction, attenuate the increase in plasma cytokine and chemokine levels induced by sepsis, inhibit lung and renal vascular leakage in vital organs, and improve the survival rate of mice with sepsis [27]. In the mouse kidney ischemia/reperfusion injury model, the level of urinary extracellular ATF3 (activating transcription factor 3) was detected to be higher than normal before serum creatinine concentration had increased [28].…”
Section: Exosomes Play a Role In Important Organ Damage In Patients Wmentioning
confidence: 90%
“…As they can circumvent endocytosis and escape from phagocytosis by the RES, exosomes have high delivery efficacy. In a recent study, endothelial progenitor cell-derived exosomes containing abundant miRNA-126-3p and 5p could attenuate organ injury and vascular permeability in cecal ligation and puncture (CLP)-induced sepsis [103]. In another study, Wen et al utilized human bone marrow mesenchymal stem cells (hBMSCs) and their exosomes (which are rich in siFas and anti-miRNA-375) to restrain islet apoptosis and primary nonfunction (PNF) during islet transplantation in humanized NOD scid gamma (NSG) mice [104].…”
Section: Cell-derived Membrane Vesiclesmentioning
confidence: 99%